The expected effects in allowing the Saudi women to drive cars from the point of Saudi university students - Abualola, Turki Hassan; Mostafa, Elsayed Ibrahim (Journal of Humanities & Social Sciences, 2021)
This current research aims to identify the expected effects in allowing Saudi women to drive cars from the personal level, familial, social, economic, environmental, health, educational perspectives as well as the international one. This research is descriptive based on the social survey. (11) Universities selected randomly from the total of Saudi Government Universities and a deliberated sample of female students (1590) from the theoretical and practical colleges. The results showed that the most important effects associated with women driving a car on the personal level: (achieving personal needs, self-reliance, responsibility, independence, increasing self-confidence, empowerment), and the results indicated that the most important effects associated with women driving on the family level: (Achievement Family tasks, family's participation in the tasks, activities of daily life, the preservation of family privacy and the preservation of family secrets). The results also showed that the most important effects associated at the societal level are: (changing the negative mental image towards women and achieving adaptation and social integration of women and a sense of social participation. The results showed that the most important impacts on the economic level are: (saving expenses of the transportation and the private driver and taxi, reducing the migrant of workers and increasing job opportunities).
Keywords: driving; expected effects